Development of the Islamic insurance business in Malaysia - Ab Rahman, Asmak; Mohamad, Shamsiah; Wan Ahmad, Wan Marhani; Hussin, Mohd Fauzi (2011)
Muslims are prohibited from taking conventional insurance due to some forbidden elements in the conventional insurance. Given the undoubted importance of insurance for risk management, Muslim scholars suggested that Islamic insurance should be introduced to fulfil the need of Muslims. After the establishment of the first Islamic insurance company in the Sudan, Islamic Insurance has developed rapidly all around the world. This paper aims to study the development of Islamic Insurance in Malaysia in terms of the increase in the number of takaful and retakaful companies, the development of takaful business compared to conventional insurance, developments in takaful models, and the diversified takaful plans being offered. This study utilises documentation and historical methods. The results of this study reveal that after 26 years of takaful operation in Malaysia, there are now ten takaful companies, four retakaful companies and an increasing number of takaful policies taken up by Malaysians. Malaysia also signifies its presence in the takaful market, being the second largest takaful market in the world, as its total assets of US$3.2 billion dominated 26 percent of total global takaful assets in 2009. Nevertheless, conventional insurance remains predominant in Malaysia’s insurance industry, where we can see that out of the 53.5 percent market penetration rate for both takaful and insurance, the market penetration rate for takaful was merely 10.9 percent in September 2010.